Comparison Between Norepinephrine-Epinephrine and Norepinephrine-Vasopressin Effectiveness in Reducing Mortality in Septic Shock: A Systematic Review - Tan, Kenneth; Benedictus, Benedictus; Purnomo, Christopher William (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background: Sepsis is a state of organ dysfunction caused by the immune system’s abnormal response to an infection. Septic shock is sepsis complicated by circulatory and metabolic abnormalities, oftentimes resulting in death. Prompt identification and treatment of septic shock is crucial for the survival of patients. The latest international guideline recommends the administration of norepinephrine as the first line vasopressor, with the addition of epinephrine or vasopressin as an aid in achieving the target MAP (Mean Arterial Pressure).Methods: This study is a systematic review of literatures from the databases Pubmed PMC, Science Direct, and Proquest. Systematic reviews on septic shock, norepinephrine, and epinephrine or vasopressin were among the inclusion criterias. This resulted in a total of five systematic reviews to be included in the qualitative synthesis.Results: The five included studies were not in sync as to which vasopressor is best used for the treatment of septic shock patients. One of which did not compare the two combinations within the same category, two of which favored the use of norepinephrine-epinephrine, and the other two favored the use of norepinephrine-vasopressin for the treatment of septic shock patients.Conclusion: The existing evidence were insufficient to give a conclusion of the best combination of vasopressors for septic shock patients. More research, specifically randomized controlled trials, needs to be conducted on this topic with well defined administration of combinations of vasopressors as an advancement of this systematic review. The writers also recommend the delay of anymore systematic reviews until the former recommendation has been met.